THE REALITY OF SHARIA BANKING IN INDONESIA; CRITICAL ANALYSIS OF SHARIA ECONOMIC LAW PERSPECTIVE - Khasanah, Karimatul; Khikmah, Nurul (Universitas Muhammadiyah Surabaya, 2022)
Â This article highlights the criticism directed at Islamic banks where many parties think there is no difference between Islamic banking and conventional banks. This assumption comes from at least three realities, firstly, Islamic bank capital comes from conventional banks, secondly, mudarabah which in its implementation, banks provide non-goods funds, and thirdly, Islamic bank products that use mudarabah in practice are different from the theory of mudarabah in classical fiqh. The perspective of Islamic economic law is appropriate to be used to answer these problems. The type of research used in this paper is normative legal research. The data sources used in this paper are primary data in the form of laws and Islamic legal literature. The type of approach in this paper is a conceptual approach, the concept intended is the theories that exist in Islamic law, specifically the theory of mixing halal and haram, the concept of mudharabah and murabahah according to fiqh. This study uses a qualitative method with a literature review approach (library research). The results of the study conclude that Islamic banking capital originating from conventional banks does not damage the contracts made by Islamic banking. Murabahah and mudarabah contracts which in their application are different from classical fiqh theory are actually forms of contract innovation because they adapt to current needs and as a form of embodiment of the principles that exist in sharia economic law.